Competition in a Variety Seeking Market With Brand Name Awareness. (April 2021) - Xiong, Liyang; Yu, Honglei; Wang, Zhanqing
This article investigates service and price competition in a variety seeking market, with the consideration of brand name awareness on consumers. Variety seeking behavior is modeled as a decrease in the willingness to pay for product purchased on the previous occasion. Under a three-stage Hotelling-type model, we show that variety seeking intensifies the competition when both firms are equally known. However, when one firm is better known than the other, it softens the competition observing the differentiation of equilibrium policies. In addition, variety seeking increases both the price and service gaps to exaggerate market differentiation. Under both scenarios firms adjust the service level in the second period so as to prevent consumers from switching, if keeping prices committed across periods. Furthermore, if consumers on average have a higher propensity to one firm, the variety seeking behavior leads to a higher total profits and a higher consumer surplus.